Commissioning for nuclear power plants. (Safety standards series. Specific safety guide., 2014)
"This Safety Guide provides recommendations on the basis of international best practices, as currently followed in IAEA Member States, on how to meet the requirements for the commissioning for nuclear power plants. These requirements enable the commissioning of a nuclear power plant to proceed safely and to a high quality. The recommendations will also enable the necessary assurances to be provided that the plant has been constructed in accordance with the design intent and can be operated safely."--Publisher's description.